Activity‐Directed Synthesis of Inhibitors of the p53/hDM2 Protein–Protein Interaction. Issue 47 (4th August 2020) - Green, Adam I.; Hobor, Fruzsina; Tinworth, Christopher P.; Warriner, Stuart; Wilson, Andrew J.; Nelson, Adam
Abstract: Protein–protein interactions (PPIs) provide a rich source of potential targets for drug discovery and biomedical science research. However, the identification of structural‐diverse starting points for discovery of PPI inhibitors remains a significant challenge. Activity‐directed synthesis (ADS), a function‐driven discovery approach, was harnessed in the discovery of the p53/ h DM2 PPI. Over two rounds of ADS, 346 microscale reactions were performed, with prioritisation on the basis of the activity of the resulting product mixtures. Four distinct and novel series of PPI inhibitors were discovered that, through biophysical characterisation, were shown to have promising ligand efficiencies. It was thus shown that ADS can facilitate ligand discovery for a target that does not have a defined small‐molecule binding site, and can provide distinctive starting points for the discovery of PPI inhibitors. Abstract : Activity‐directed synthesis (ADS) was harnessed in the discovery of the p53/ h DM2 protein–protein interaction. Four novel series of PPI inhibitors were discovered that had promising ligand efficiencies. It was demonstrated that ADS can enable scaffold hopping, and facilitate lead discovery for targets lacking defined small‐molecule binding sites.